Analisis Multidimensi Chikan (Pelecehan Seksual) di Transportasi Kereta Api Tokyo: Menelusuri Faktor Lingkungan, Sosial-Budaya, dan Hukum - Alif Hafidz Putra Prayitno; Bayu Aryanto (Vocational College of Diponegoro University, 2026)
This study aims to holistically analyze the Chikan phenomenon in Tokyo's train transportation by identifying multidimensional driving factors and evaluating the effectiveness of existing countermeasures. The research employs a Mixed Methods approach with a Convergent Parallel design, where quantitative and qualitative data are collected simultaneously and integrated through cross-validation. Findings reveal that the issue is driven by the dynamic interaction of environmental factors such as extreme physical congestion providing anonymity, socio-cultural factors including stigma that leads to low reporting rates of approximately 80%, legal challenges in providing proof, and psychological factors related to frotteurism among perpetrators. The study concludes that one-dimensional technical solutions, such as Women-Only Cars, are insufficient to fully eradicate the culture of harassment as they only serve as short-term symptom management. Consequently, an integrated approach encompassing legal reform, anti-stigma social education, and clinical rehabilitation for perpetrators is necessary to address the root causes sustainably.